2013
DOI: 10.1093/icvts/ivt361
|View full text |Cite
|
Sign up to set email alerts
|

Early and late outcomes of total repair of tetralogy of Fallot: risk factors for late right ventricular dilatation

Abstract: Total correction of TOF can be performed with a very low mortality rate. However, the postoperative re-operation or re-intervention rates remain relatively high. Late RV dilatation after total repair of TOF was found to be associated with transannular patch enlargement and a longer postoperative ventilator support period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 22 publications
5
31
0
1
Order By: Relevance
“…Kim et al. [19] reported a 5% incidence of pleural effusion that required tapping. The surgical techniques for primary repair to preserve RV function, reduce arrhythmia, and optimize functional status that are still evolving and a definitive consensus is lacking [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al. [19] reported a 5% incidence of pleural effusion that required tapping. The surgical techniques for primary repair to preserve RV function, reduce arrhythmia, and optimize functional status that are still evolving and a definitive consensus is lacking [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have concluded that TAP repair is a risk factor for late RV dilatation, ventricular arrhythmias and SCD in patients who have undergone repair of TOF (15,16). TAP repair provides excellent relief of the RVOT obstruction in TOF patients, but it can results in PR.…”
Section: Discussionmentioning
confidence: 99%
“…Repair of the PV (after the TAP procedure) is the most suitable of options for reconstruction of the RVOT. 16 It is important to stress that the median age of repair in this group of TOF patients is 11 years, forming a subset that has not undergone evaluation in the aforementioned studies. Because of this deficiency in research, the progress of PI in this group cannot be predicted by available data.…”
Section: Discussionmentioning
confidence: 99%